PRAGMATISM VERSUS PRINCIPLE: MASLAHAH MURSALAH ANALYSIS OF MUSLIM STREET VENDORS' PREFERENCES FOR CONVENTIONAL MICROFINANCE INSTITUTIONS AMID THE AVAILABILITY OF ISLAMIC ALTERNATIVES - Diniatus Wahyuning Suminar; Dewi Masita (IZZI: Jurnal Ekonomi Islam, 2025)
This study examines a striking paradox observed in Sebani Village, Gadingrejo District, Pasuruan City, East Java, Indonesia: the overwhelming majority of Muslim street vendors (known locally as Pedagang Kaki Lima, or PKL).Through a rigorous qualitative methodology comprising in-depth semi-structured interviews, participatory observation, and systematic documentation of 15 active borrowers and two financial institution officers, this research reveals that financial decision-making among this population is driven primarily by operational factors: service accessibility, speed of fund disbursement, procedural simplicity, and the proactive door-to-door outreach model of Mekaar's field agents. Theological considerations regarding the halal or haram nature of transactions were largely absent from borrowers' deliberative processes, a finding that reflects deep structural deficiencies in Islamic financial literacy at the grassroots level. The scholarly novelty of this research lies in its deployment of the maslahah mursalah framework as a concrete normative analytical instrumentnot merely as a theoretical backdropto evaluate the Shar'i legitimacy of these pragmatic choices within the broader maqashid al-Shari'ah perspective. The analysis reveals that PNM Mekaar's financing practices fulfill the maqashid dimensions of hifzh al-mal (protection of wealth), hifzh al-nafs (protection of life), and hifzh al-'aql (protection of intellect) as genuine hajiyyah-level maslahah. However, the practice carries serious risks concerning hifzh al-din (protection of religion) due to contractual ambiguity, administrative fee structures that functionally mirror conventional interest, and the complete absence of Islamic financial education. The study concludes that Islamic financial institutions must undergo fundamental service transformation centered on grassroots community needs, and that enhancement of Islamic financial literacy constitutes a structural prerequisitenot an optional policy measurefor the effectiveness of the Islamic financial system in Indonesia.